The Influence of Financial Attitude, Financial Technology, Locus of Control and Hedonic Lifestyle on Financial Behavior (Study on Management Study Program Students, Tribhuwana Tunggadewi University, Malang) - Reineldis Jemanis Amat; Elly Lestari; Moch Nurhidayat (International Research and Development for Human Beings (IRDH), 2025)
This study aims to analyze the influence of financial attitude, financial technology, locus of control, and hedonic lifestyle on the financial behavior of students at Tribhuwana Tunggadewi University, Malang. Using a quantitative approach, this study involved 70 respondents selected through a simple random sampling method from a population of 229 students of the Management study program, class of 2021-2022. Data collection was carried out through observation, documentation, and questionnaires with a Likert scale, while data analysis used multiple regression. The results showed that financial attitude and hedonic lifestyle had a significant effect on students' financial behavior, while financial technology did not have a significant effect. Locus of control had a positive but insignificant effect on financial behavior. Overall, students with good financial attitudes, optimal use of financial technology, and good self-control tended to have more structured and planned financial behavior. However, a high hedonic lifestyle can increase the risk of ineffective financial management.